Combination of different antifungal agents in oil-in-water emulsions to control strawberry jam spoilage. (15th January 2018) - Ribes, Susana; Fuentes, Ana; Talens, Pau; Barat, Jose Manuel
Highlights: Cinnamon bark oil, zinc gluconate and trans -ferulic acid were used as antifungals. Innovative delivery systems formulated with different antifungal agents were studied. Emulsions' impact on the sensory profile of strawberry jam was tested. Hygienic quality of strawberry jam was maintained using novel emulsions. The profile of the strawberry jam was not affected by emulsions' addition. Abstract: The combination of antifungal agents (cinnamon bark oil, zinc gluconate and trans -ferulic acid) in oil-in-water emulsions to control the fungal spoilage of strawberry jams, minimising essential oil's sensory impact, was evaluated in this work. The in vitro assays of free antifungal agents were performed against five fungal strains; meanwhile, the emulsions assays were conducted against Aspergillus niger given its strong resistance and its relevance in strawberry products. The emulsion formulated with 0.08 mg/g of essential oil was able to inhibit mould growth after the incubation period. The incorporation of zinc gluconate or trans -ferulic acid, independently of the concentration used, allowed to reduce a 25% the amount of essential oil needed to inhibit the microbial growth. The combination of antifungal agents in the emulsions has demonstrated to be an effective alternative to reduce the amount of essential oil employed, maintaining the hygienic quality and sensory profile of the strawberry jam.